19.04: Diagrid: the renaissance of steel structures for tall buildings geometry, design, behavior. (13th September 2017) - Mele, Elena
ABSTRACT: Structural configurations best addressing the traditional requirements of strength and stiffness for tall buildings are the ones employing the tube concept, whose efficiency, however, is strictly related to the involved shear‐resisting mechanism. In this perspective, diagrid structures – the latest mutation of tube structures – show an extraordinary efficiency, related to the adopted geometrical pattern: thanks to the triangle tessellation of the façades, internal axial forces are largely prevalent in the structural members, thus shear lag effects and racking deformations are minimized. Being also adaptable to whatever surface, diagrid is becoming the most used structural solution for tall buildings of complex form. In this paper some specific design issues for diagrid structures are identified, namely: the relative importance of strength and stiffness design criteria, as well as to the need of secondary bracing systems for counteracting the inter‐module flexibility effects. Simplified procedure for dealing with such issues are proposed and design implications are discussed.